The relationship between repetitive motion and level of fatigue among weaver craftsman - Imam Rangga Yudhistira; W. Wahyuni (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: The weaving process is a repetitive activity because of the repetitive hand movement pattern with a load period of < 3 kg. Work patterns that do not pay attention to ergonomics will cause problems such as fatigue, injury, musculoskeletal disorders, work accidents, and issues due to excessive repetitive motion. This study aimed to determine the relationship of repetitive motion to the level of fatigue in weaving workers. Methods: This study used a cross-sectional approach using a sample of 44 weaving artisans who joined the association in the Special Region of Yogyakarta. This study used non-parametric statistical tests with Kendall Tau correlation test techniques. Results: Based on data analysis in the study, a positive correlation was obtained with a significance value of p= 0.001 (p< 0.05), which means a significant positive correlation exists between repetitive motion and fatigue level in weaving workers. Conclusion: Based on the results of research and discussion, it can be concluded that there is a relationship between repetitive motion and fatigue in weaving artisans in the Special Region of Yogyakarta. It is also proven by the Kendals Tau test, which has a p-value = 0.001 or p< 0.050, so it can be said that there is a relationship between repetitive motion and fatigue in weaving artisans in Yogyakarta.